Da ação social a relação social: estudo das práticas de comunicação no Complexo Industrial de Barcarena - PRESSLER, Neusa Gonzaga de Santana (2004)
This research paper investigates the communication practices adopted by the Companies Albras-Alunorte located in Barcarena - Pa. With this proposal, it investigates how the practice of institutional communications strategies can improve and generate values in the relations between those companies and their strategic publics, collaborating to maintain their identity and institutional image in Amazonia as well as in the International Market. This study intends to answer one of the many social communications contradictions in those companies, after the implement of those so called Big projects. The changes that took place in the area where those big mining companies are, were noticeable in may ways, like: initiating new relationship ways between the existing social actors and the new ones that arrived accordingly to the companies administration. Therefore, the arrivel of those big projects modifies the way of life, the new relationship with land and environment, and also of changes the interpersonal relationships in institutional and social communications. So, it is desirable to describe the path followed by these companies throw the practices of the institutional communication. In this way, the research will describe those communicational practices that changed the social actions to the actual social relations, and also, how these companies built and maintained this identities and institutional images.